2016
DOI: 10.1111/anae.13578
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intra‐operative maintenance of general anaesthesia with propofol on postoperative pain outcomes – a systematic review and meta‐analysis

Abstract: SummaryPropofol is used both for induction and maintenance of anaesthesia. Recent evidence shows that propofol has analgesic properties. This meta-analysis evaluated differences in postoperative analgesia between general anaesthetic maintenance with intravenous propofol and inhalational anaesthetics. Fourteen trials met inclusion criteria and were included. Our outcomes were pain scores 2 and 24 h after surgery. No significant difference in pain scores was found at 2 h after surgery (Hedge's g (95% CI) À0.120 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 41 publications
2
53
2
Order By: Relevance
“…The atmospheric temperatures in the operating theatre and the recovery area were not significantly different. Propofol and remifentanil are known to have short context‐sensitive decrement times . Second, this new index has not yet been confirmed to work well during general anaesthesia.…”
Section: Discussionmentioning
confidence: 93%
“…The atmospheric temperatures in the operating theatre and the recovery area were not significantly different. Propofol and remifentanil are known to have short context‐sensitive decrement times . Second, this new index has not yet been confirmed to work well during general anaesthesia.…”
Section: Discussionmentioning
confidence: 93%
“…The lack of standardisation of pain outcomes is not limited to paediatric populations, however. A recent systematic review of propofol for postoperative pain reported that seven primary studies could not be included as the different pain scoring systems were not interconvertible . This lack of consistency in pain measurement in adults suggests that standardisation for pain assessment is needed in all patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, with TIVA, we control anaesthesia/consciousness with one drug (propofol) and analgesia with another (a titratable opioid such as remifentanil). Propofol is a powerful hypnotic drug but not a conventional analgesic , although it does have activity at hyperpolarisation‐activated cyclic nucleotide‐gated channel‐1 (HCN1) receptors and anti‐inflammatory effects which reduce postoperative pain . This is an important distinction but one which may also have advantages now that there is increasing concern over the adverse effects of excessively deep anaesthesia .…”
Section: Lost In Translationmentioning
confidence: 99%
“…Quality of recovery is one of the most obvious, well‐known and tangible benefits of propofol‐based TIVA, but others are becoming apparent. Patients appear to have less pain than after inhalational anaesthesia and there is less impact on neurocognitive function . There may even be survival advantages in cancer surgery , with plausible mechanistic support .…”
mentioning
confidence: 98%